Off Label and Unlicensed Drug Prescriptions in Pediatric Medical Units at Tertiary Care Hospitals of Peshawar, Pakistan - Aamir, Muhammad (International Journal of Pathology, 2022)
Background: Off label and unlicensed prescribing is a global dilemma. The study was designed to investigate the prevalence and predictors of off label and unlicensed prescriptions in pediatric medical wards of Peshawar.Materials & Methods: A prospective, cross-sectional survey was performed over a year in the pediatric medical units of four tertiary care hospitals in Peshawar. Drug profiles of 1375 patients were evaluated by Micromedex.Results: A total of 100 different drugs were prescribed 5708 times to patients admitted in pediatric medical wards, of which 34.34% prescriptions were unlicensed and 52.99% prescriptions were off labelled. Regression analysis revealed that patients prescribed with ≥5 drugs (OR 0.113; CI 0.041-0.312) had 89% higher odds of receiving unlicensed medications as compared to children receiving <5 medications, while patients with a hospital stay of duration ≥4 days (OR 0.423; CI 0.238-0.752) had 58% higher odds of receiving unlicensed drugs.Conclusion: Considerably high prevalence of unlicensed and off label drug prescribing was observed in the medical wards of pediatric department. There is need of improved prescribing strategies to reduce unlicensed and off label prescriptions to ensure better health care of children